Estudio de factibilidad para la producción y comercialización de pollos criollos en el cantón La Joya de los Sachas, provincia de Orellana, para el año 2017 - Romero Trujillo, Tania Maritza (2017)
At the moment the canton the Joya de Sachas of the province of Orellana is affected by a notorious recession in the productive field, being a barrier for its sustained development and that allows to compete with other cantons and provinces of the country. This research is about the creation and elaboration of a proposal for the implementation of a company dedicated to the production and commercialization of Creole chickens in the canton Joya de los Sachas. This is how the research provides all the steps and studies that help define the effectiveness of the project. For these reasons, this project aims to help with the implementation of a company that allows to create some sources of work, take advantage of existing natural resources, creating an economic value added and put into practice the knowledge acquired, for the benefit of a society that needs its new professionals are inserted in productive and economic life. Hence the real need to produce goods and services, being entrepreneurs and facing the serious crisis that crosses our country, being convenient to carry out and execute the thesis project called: "FEASIBILITY STUDY FOR THE PRODUCTION AND MARKETING OF CRYOLLOS POLLOS, IN CANTON THE JEWEL OF THE SACHAS, PROVINCE OF ORELLANA, FOR THE YEAR 2017 "the same that contributes to the development of this canton. The complete analysis of the project was carried out based on the following studies and analyzes: market study, technical study, administrative and legal study, economic and financial study and finally the valuation of the project. The market study analyzes supply and demand. For all of these, a survey was conducted both for the claimants and also for the bidders, to determine the unsatisfied demand that is 468488 chickens for the first year, the installed capacity is 28800 and the capacity used is 27792 for the first year with a mortality rate of 3.50%. Administrative and legal study of the company makes it easy to determine the business group, constitution, organization and function manuals. The company will make the trade under the name "CROLLE CREOLE LAKE SAN PEDRO JOYA DE LOS SACHAS. INC. LTDA. "Its mission It will be the production and commercialization of chicken criollos, to satisfy with quality and competitive prices the demand of the canton Joya de los Sachas. Economic and financial study to know about the investment of the project investment in fixed assets of 74723.25, Deferred Assets of 1701 and working capital of 25481.84, investment financing, income and expenditure budget, cost analysis, balance and study points and analysis of the financial statements (statement of losses and gains and cash flow). Finally, the evaluation of the project was carried out to establish the suitability of the project and its execution, for which the following indicators were analyzed: Net Present Value of $ 254648.46; Internal Rate of Return of 72.75%; Profit ratio Cost is 1.19 per dollar invested the company earns 0.19 cents; Period of Capital Recovery is 1 years, 8 months and 26 days; Sensitivity Analysis indicates that the project supports an increase in costs of 2.5% giving a total of 0.9976137% and the sensitivity analysis in the decrease in revenues of 3.5% giving a total of 0.9921206% for which the project is feasible, whose conclusions and recommendations so determine, attaching the bibliography consulted with their respective annexes.